2019
DOI: 10.1111/ijac.13363
|View full text |Cite
|
Sign up to set email alerts
|

The gadolinium effect on crystallization behavior and luminescence of β‐NaYF4:Yb,Er phase

Abstract: Single phase β-NaY 0.8-x Gd x Yb 0.18 Er 0.02 F 4 nanoparticles with different concentrations of gadolinium ions were prepared via PVP-assisted solvothermal treating at 200°C (PVP-polyvinylpyrrolidone). With the increase in Gd 3+ concentration, size of the nanoparticles decreased. The up-converting spectra recorded upon 980 nm irradiation showed the green (510-560 nm) and red (640-690 nm) emissions, due to 2 H 11/2 , 4 S 3/2 → 4 I 15/2 and 4 F 9/2 → 4 I 15/2 transitions, respectively. The strongest up-conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…Earlier studies demonstrated that the Yb 3+ optimal concentration is about 20 at % [ 23 , 24 , 25 ]. Our preliminary experiments demonstrated that in NaY 0.8-y Yb 0.20 Tm y F 4 and NaY 0.8-z Yb 0.20 Er z F 4 , the optimal concentration of Tm 3+ and Er 3+ is in the range of 0.5–1 at %, which agrees with earlier studies where the optimal dopant concentration for Tm 3+ and Er 3+ ions varied from 1% to 2% [ 18 , 20 , 22 , 23 ]. Therefore, in this work, we synthesized and studied the two Gd 3+ co-doping series of upconverting microcrystals with 1% Tm 3+ /Er 3+ concentration: NaY 0.79−x Yb 0,20 Tm 0.01 Gd x F 4 and NaY 0.79−x Yb 0,20 Er 0.01 Gd x F 4 (x = 0–0.2).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier studies demonstrated that the Yb 3+ optimal concentration is about 20 at % [ 23 , 24 , 25 ]. Our preliminary experiments demonstrated that in NaY 0.8-y Yb 0.20 Tm y F 4 and NaY 0.8-z Yb 0.20 Er z F 4 , the optimal concentration of Tm 3+ and Er 3+ is in the range of 0.5–1 at %, which agrees with earlier studies where the optimal dopant concentration for Tm 3+ and Er 3+ ions varied from 1% to 2% [ 18 , 20 , 22 , 23 ]. Therefore, in this work, we synthesized and studied the two Gd 3+ co-doping series of upconverting microcrystals with 1% Tm 3+ /Er 3+ concentration: NaY 0.79−x Yb 0,20 Tm 0.01 Gd x F 4 and NaY 0.79−x Yb 0,20 Er 0.01 Gd x F 4 (x = 0–0.2).…”
Section: Methodssupporting
confidence: 91%
“…In our work, we partially substituted Yb 3+ by Gd 3+ ions in NaYF 4 : Yb 3+ , Tm 3+ /Er 3+ materials to improve upconverting properties. It was previously demonstrated that Gd 3+ co-doping improves the luminescent properties of rare earth-based materials [ 17 , 20 ]. By introducing Gd 3+ ions into the NaYF 4 crystal lattice, it is possible to change local symmetry, thus increasing the probability of energy transfer processes, which could increase luminescence intensity.…”
Section: Introductionmentioning
confidence: 99%
“…According to the phase diagram of NaF-YF 3 and YF 3 -GdF 3 systems [38], the crystallization of the following fluorides could be achieved in function of temperature, NaYF 4 in two forms (cubic α phase, Fm-3m; and hexagonal β phase, P63/m), and three crystal structures of the Y 1−x Gd x F 3 phases (orthorhombic β phase, Pnma; hexagonal, P63cm; and trigonal, P-3c1 phase). Contrary to our previous work, where we obtained the β-NaYF 4 :Yb,Er phase under identical processing conditions [39], since the YF 3 and GdF 3 phases show complete miscibility, all samples synthesized in this study, independent of stoichiometry, have the same orthorhombic crystal structure. The XRPD analysis revealed a change in the unit cell parameters due to the substitution of ytterbium by gadolinium and the coexistence of two different particle populations in all samples, which is associated with the formation of monocrystals.…”
Section: Discussioncontrasting
confidence: 63%
“…The most optimal excitation for upconverting hosts doped with Erbium (Er) and Ytterbium (Yb) occurs at the 980 nm wavelength [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%